DEVELOPING LISTENING PROFICIENCY THROUGH FILMS AND TELEVISION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the innovative use of films and TV shows as tools forteaching and improving listening skills in language learning. It highlights the benefits of thesemedia, such as exposure to authentic language, diverse accents, and contextual learning, allwhile maintaining student engagement. The article provides practical strategies for integratingvisual media into lessons, including using subtitles, analyzing scenes, and conductinginteractive activities like shadowing and role-playing. Additionally, it addresses commonchallenges, such as fast-paced dialogue and vocabulary overload, offering solutions toovercome them. Concluding remarks emphasize the dual role of films and TV shows infostering linguistic proficiency and cultural awareness, making them invaluable resources forboth